Kajian Eksperimen Pengaruh Lingkungan Panas Terhadap Suhu Kulit Manusia Menggunakan Fast Response Temperature Probe PS-2135 dan Temperature Array PS-2157 - Kolibu, Hesky Stevy; Suoth, Verna Albert (Jurnal MIPA, 2019)
Fisika  merupakan  ilmu  alam  yang  saling  berkaitan  dengan  ilmu  lainnya. Salah  satu keterkaitannya  mempelajari  sistem  adaptasi  tubuh  manusia  terhadap  perubahan  suhu. Suhu kulit adalah faktor mendasar dalam pertukaran panas antara tubuh dan lingkungannya. Tingkat suhu kulit secara langsung mempengaruhi transfer energi oleh konveksi dan radiasi dan juga memengaruhi kehilangan panas dari penguapan keringat. Dalam studi eksperimental ini, nilai perubahan suhu kulit dikumpulkan menggunakan Fast Response Temperature Probe PS-2135 dan Temperature Array PS-2157. Tujuan dari studi ini adalah untuk menyelidiki efek dari lingkungan panas pada respon fisiologis suhu kulit tubuhPhysics is a natural science that is interrelated with other sciences. One connection is studying the human body's adaptation system to temperature changes. Skin  temperature  is  a  fundamental  factor  in  heat exchanges  between  the  body  and  its  environment. The level  of  skin  temperature  directly  affects  the energy  transfer  by  convection  and  radiation  and also  influences  heat  losses  from  sweat  evaporation. In this experimental study, the skin temperature changes values are collected using Fast Response Temperature Probe PS-2135 and Temperature Array PS-2157. The purpose of this study was to investigate the effects of warm environmental on physiological responses of body skin temperaturePhysics is a natural science that is interrelated with other sciences. One connection is studying the human body's adaptation system to temperature changes. Skin  temperature  is  a  fundamental  factor  in  heat exchanges  between  the  body  and  its  environment. The level  of  skin  temperature  directly  affects  the energy  transfer  by  convection  and  radiation  and also  influences  heat  losses  from  sweat  evaporation. In this experimental study, the skin temperature changes values are collected using Fast Response Temperature Probe PS-2135 and Temperature Array PS-2157. The purpose of this study was to investigate the effects of warm environmental on physiological responses of body skin temperature